2020
DOI: 10.1002/pne2.12015
|View full text |Cite
|
Sign up to set email alerts
|

Creating online animated videos to reach and engage youth: Lessons learned from pain science education and a call to action

Abstract: Education is a keystone of many therapies for youth. Clinicians are expected to provide effective education that translates across multiple learning styles and developmental stages. High-quality animations provide an ideal opportunity to engage youth in health education online. Animations are particularly well-suited for illustrating abstract or hard-to-visualize phenomena relevant to health science, such as neuroanatomy and brain functions. Video animations also have the additional benefit of being able to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
(50 reference statements)
1
20
0
1
Order By: Relevance
“…Such positive effects were particularly salient in attracting more positive feedback of youths, which indicated youths' praise and support when noticing recreational videos made by government accounts. This finding proves the effectiveness of engaging youths through recreational videos under the context of crisis, which is consistent with the successful practice of EE in other areas such as health education ( Martzoukou, 2020 ; Pate et al, 2020 ; Shigehatake et al, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such positive effects were particularly salient in attracting more positive feedback of youths, which indicated youths' praise and support when noticing recreational videos made by government accounts. This finding proves the effectiveness of engaging youths through recreational videos under the context of crisis, which is consistent with the successful practice of EE in other areas such as health education ( Martzoukou, 2020 ; Pate et al, 2020 ; Shigehatake et al, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
“…For instance, Shigehatake et al revealed that the animated cartoon could successfully improve education of Stroke knowledge in high school students ( Shigehatake et al, 2014 ). Also, Pate et al argued that high-quality online animated videos were a potentially excellent medium to engage youth at a mass level in pain science education ( Pate, Heathcote, Simons, Leake, & Moseley, 2020 ). Martzoukou investigated using cartoon videos to promote youths' development of digital literacy, resilience and citizenship in the online environment, and revealed its positive effects ( Martzoukou, 2020 ).…”
Section: Theoretical Foundations and Hypothesismentioning
confidence: 99%
“…In addition to one-to-one conversation, online educational videos or online therapy sessions provide an ideal opportunity to engage youth in pain education [ 83 ]. Young people are growing up in an advanced technological age and are using digital media to answer their health questions [ 84 ].…”
Section: Which Methods Are Helpful For Delivering Pain Education?mentioning
confidence: 99%
“…Videos can be easily disseminated online, which removes time-consuming and physical limitations of face-to-face delivery methods. 103 For example, "The Mysterious Science of Pain" 104 is a freely available YouTube video for children and adolescents to begin exploring biopsychosocial factors that can influence the way humans experience pain and how the nervous system acts toward potentially harmful stimuli. Overall, although concepts and language used in current resources are not specific to cancer-related pain, recent advancements and developed tools to deliver PSE to children and adolescents could provide a strong foundation for the development and implementation of PSE in children with cancer-related pain.…”
Section: 21mentioning
confidence: 99%